THE INFLUENCE OF CRITICAL THINKING SKILL AND LEARNING INDEPENDENCE ON STUDENT LEARNING OUTCOMES - Heriyanti; Basri; Hamka (CV. Fahr Publishing, 2024)
Outcomes. Academic Year 2022/2023. Thesis. Muhammadiyah Bone University Economic Education Study Program. Supervised by Supervisor Ir. Basri M.Si and Supervisor II Hamka, S.E.M Si. This research aims to determine: (1) the influence of critical thinking skills partially on student learning outcomes, (2) the influence of partial learning independence on student learning outcomes and (3) the influence of critical thinking skills and learning independence simultaneously on student learning outcomes. results. This research was carried out at SMA Negeri 18 Bone. The research approach is ex post facto. The population in this study were all students in class XI IIS of SMA Negeri 18 Bone, totaling 32 people consisting of 18 men and 14 women. The sample was determined using full sampling. The data analysis used in this research is multiple regression analysis. The results of the research show that: Critical thinking skills have a partially positive and significant effect on the learning outcomes of SMA Negeri 18 Bone students, because the P-value is 0.000 < 0.05 or the calculated t value is 6.521 > t table in df (30) is 2.042. Learning independence has a partially positive and significant effect on the learning outcomes of SMA Negeri 18 Bone students, because the P-value is 0.001 < 0.05 or the calculated t value is 3.760 > t table in df (30) is 2.04. The ability to think critically and independently learn simultaneously has a positive and significant effect on the learning outcomes of SMA Negeri 18 Bone students as indicated by a significant value of 0.00 (sig 0.00 < 0.05) and a calculated F value of 119.915 > the F table value in df (2)(30) is 19.50.